SOME GENERAL AND SPECIAL CASES IN THE ART OF TRANSLATION (World Bulletin of Social Sciences, 2024)
This article discusses linguistic problems of translation, written and oral translation, interlingual differences and translation (terms of kinship), linguistic and non-linguistic problems of translation, comparative grammar and comparative methodology, gender category in translation, types and types of translation, areas and genres are discussed. talk about lines